Social Presence in Omega-3 Supplement Marketing: Elaboration Likelihood Processing Among Young Adults - Triyanti, Vivi; Halimin, Aretha Jerika; Sukwadi, Ronald; Silitonga, Riana Magdalena; Hutahaean, Hotma Antoni; Yee, Yann-Mey; Thu, Nguyen Thi Bich (Indonesian Journal of Business and Entrepreneurship, 2026)
Backgrounds: The high prevalence of cholesterol in young adults has increased the popularity of dietary supplements. Brochures, both online and offline, are common mediums for communicating product benefits. As humans are inherently social, incorporating social presence into product visuals may enhance user engagement.Purpose: This study examines the effect of varying levels of social presence in omega-3 supplement photographs on consumers’ emotional valence, emotional arousal, and perceived product diagnosticity using the Elaboration Likelihood Model to distinguish between central and peripheral processing routes.Design/methodology/approach: This study hypothesizes that social presence influences peripheral variables emotional valence and emotional arousal as well as the central variable of product diagnosticity. Fifteen questionnaire items measured these constructs across three social presence scenarios (low, moderate, and high). A total of 114 participants who were familiar with omega-3 supplements and had experience using Instagram were recruited for the study. Data were analyzed using the Friedman test to identify differences between conditions.Findings/Result: Significant differences were observed across social presence levels. Images with high social presence generated the strongest positive emotional valence and arousal, whereas images with low social presence resulted in superior product diagnosticity. The moderate social presence condition yielded comparatively lower scores across all variables, suggesting limited effectiveness in activating either processing route.Conclusion: High social presence effectively elicits emotional valence and arousal through peripheral processing, whereas low social presence enhances product diagnosticity via central processing. Moderate social presence failed to strongly activate either route, underscoring the strategic role of visual social cues.Originality/value (State of the art): This study offers actionable insights for designing health supplement brochures that balance emotional appeal and cognitive clarity, advancing research on social presence and consumer engagement in health communication and marketing.Keywords:  social presence, elaboration likelihood model, omega-3 supplement, friedman test, health supplement brochures